Ultrasonic diagnosis of delayed hematoma during emergency removal of traumatic intracranial hematoma: A case report and literature review. Issue 14 (7th April 2023) - Weng, Yan; Shang, Ziqi; Zhong, Qing
Abstract : Rationale: It is emergency and vital during neurosurgical procedure in traumatic intracranial when an acute intraoperative brain bulge (AIBB) is occurred. It is important to get a diagnosis quickly. Patient concerns: A 44-year-old man was undergone a neurosurgical procedure for the left side of traumatic intracranial hematoma. An AIBB was occurred during the surgery. Computed tomography (CT) is always used in diagnosis when an AIBB is occurred, but more time is needed when CT is conducted. Diagnoses: We diagnosed the AIBB through bedside real-time ultrasound, and a delayed hematoma which caused the AIBB was found. Interventions: A further neurosurgical procedure of right intracranial hematoma was performed for the patient. Outcomes: The surgical effect and the patient's prognosis were significantly improved. Lessons: Through this patient, we should pay more attention to the application of perioperative of real-time ultrasonic monitoring, to provide more convenience for surgical patients, and improve the prognosis of them.